Slavery unseen: sex, power, and violence in Brazilian history - Aidoo, Lamonte (Latin America otherwise, 2018)
The racial and sexual paradoxes of Brazilian slavery and national identity -- Illegible violence : the rape and sexual abuse of male slaves -- The white mistress and the slave woman : seduction, violence, and exploitation -- Social whiteness : Black intraracial violence and the boundaries of Black freedom -- O diabo preto (the Negro devil) : the myth of the Black homosexual predator in the age of social hygiene